Vibrational Properties of Sundatang Soundboard - BATAHONG, Ronald Yusri; DAYOU, Jedol; WANG, Semyung; LEE, Jongsuh (Archives of Acoustics, 2014)
This paper presents the measurement of vibrational properties of sundatang soundboard. Sundatang is a plucked stringed traditional musical instrument that is popular among the Kadazandusun communities in Sabah, Malaysia. The vibrational properties of the soundboard are measured using CADA-X impact hammering system in a condition where the instrument is without any string. There are two types of sundatang used in this study; one made from acacia and the other from vitex wood. In this measurement, frequency response functions (FRFs) and modal parameters of the top plate and back plate of this instrument are obtained. It is found that in free edge, fundamental frequency of both plates of acacia sundatang is greater than the vitex sundatang in a range of 112 Hz to 230 Hz. However, in clamped edge (attached to its ribs), it was modified to a lower frequency and closer to each other in the range of 55 Hz to 59 Hz. Another finding is the detection of the excitation of similar mode shape at different resonance frequencies. This phenomenon is termed as Different State of Mode (DSM) which is observed may be because the number of testing points is not enough. Findings of this study provide important information to the study of quality development of this instrument.